(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The gene family responsible for Parkinsonism is PARK1-PARK4-linked (α-synucleinopathies) autosomal dominant forms. Neuropathologically, deposits of filamentous protein aggregates, socalled Lewy bodies, Lewy neuritis, and intraneuronal inclusions are found in the brains of patients with Parkinson’s disease. These aggregates are found in dopaminergic neurons of the substantia nigra and other brain regions such as the cortex and magnocellular basal ganglia of the forebrain. Lewy bodies are predominantly composed of hyperphosphorylated α-synuclein protein fibrils (Masliah et al., 2000, Schell et al., 2009).